2020
DOI: 10.1002/celc.202001387
|View full text |Cite
|
Sign up to set email alerts
|

Influence and Electrochemical Stability of Oxygen Groups and Edge Sites in Vanadium Redox Reactions

Abstract: It is widely accepted that surface-active oxygen functional groups (OFGs) effectively catalyze the vanadium redox reactions. Initial graphitic edge sites, OFGs and their electrochemical stability were examined using graphite felts, which were modified with multi-walled carbon nanotubes and activated with KOH. It is demonstrated that OFGs cannot exclusively be responsible for the electrocatalysis since they did not correlate to the electrochemical activity. The surface composition after electrochemical cycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
(138 reference statements)
2
14
0
Order By: Relevance
“…The degree of oxidation at this material is high as it was studied by our group previously. 37 The oxygen-free electrodes further decrease R CT during cycling. In the positive half-cell, R CT steadily decreases with higher deoxygenation temperatures.…”
Section: Inuence Of Ofgs On the Electrochemical Half-cell Performancementioning
confidence: 96%
See 1 more Smart Citation
“…The degree of oxidation at this material is high as it was studied by our group previously. 37 The oxygen-free electrodes further decrease R CT during cycling. In the positive half-cell, R CT steadily decreases with higher deoxygenation temperatures.…”
Section: Inuence Of Ofgs On the Electrochemical Half-cell Performancementioning
confidence: 96%
“…In a previous study, we have already shown that OFGs are electrochemically unstable, and predictions on the activity cannot be made based alone on a previous physicochemical characterization. 37 To study the inuence and electrochemical performance of OFGs on graphite felt electrodes, we took a different approach compared to previously discussed studies. While usually the oxygen concentration is increased by an oxidative pretreatment, we thermally deoxygenated felt electrodes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…edge sites 2020 [6] ited several oxygen-related functional groups after activation, which were held responsible for the enhanced electron transfer properties.…”
Section: Electrochemical Activationmentioning
confidence: 99%
“…It was recently demonstrated that they are a poor activity descriptor because there was no correlation between half‐cell activity and concentration of surface oxygen moieties before or after electrochemistry. [6] Oxidative activation creates pores and corrosion‐like pits on the otherwise smooth pristine GF, as it is observed by scanning electron microscopy (SEM). If the damaging exceeds the mechanical tolerance of the material, its structural properties change and the long‐range order is lost, resulting in an amorphous material with low electrical conductivity.…”
Section: Introductionmentioning
confidence: 96%
“…In a previous study, we have already shown that OFGs are electrochemically unstable, and predictions on the activity cannot be made based alone on a previous physicochemical characterization. 37 Figure 1. Schematic representation of the graphite structure and the experimental procedure.…”
Section: Introductionmentioning
confidence: 99%